2012
DOI: 10.1136/jech-2011-200794
|View full text |Cite
|
Sign up to set email alerts
|

Asian dust storm events are associated with an acute increase in stroke hospitalisation

Abstract: The authors conclude that ADS events are associated with an acute increase in stroke admission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…29 The occurrence of Asian dust storms in Korea during early spring is a possible explanation for the increased occurrence of cardioembolic stroke during winter and spring in the present study. 30 Moreover, we observed that the incidence of cardioembolism was highest among ischemic stroke patients living in areas defined as cities, where air pollution is the highest.…”
Section: Strokementioning
confidence: 81%
“…29 The occurrence of Asian dust storms in Korea during early spring is a possible explanation for the increased occurrence of cardioembolic stroke during winter and spring in the present study. 30 Moreover, we observed that the incidence of cardioembolism was highest among ischemic stroke patients living in areas defined as cities, where air pollution is the highest.…”
Section: Strokementioning
confidence: 81%
“…In Taiwan, a statistically significant association between dust storm events and daily primary intracerebral hemorrhagic stroke admissions, and a positive but non-significant association between dust events and ischemic stroke admission three days after the event, were indicated by Yang et al [163]. Kang et al [164] found a significantly higher number of ischemic stroke admissions two days post-dust event but no difference in hemorrhagic stroke admissions. Kamouchi et al [165] also indicated that Asian dust was not significantly associated with the overall incidence of ischemic stroke, but there was a relationship specific to the stroke subtypes such as atherothrombotic brain infarction in Japan.…”
Section: Desert Dust and Cardiovascular Diseasesmentioning
confidence: 97%
“…[82] Storms are associated with increased risk of stroke hospital admissions that persists for two days following dust storms. [83] Asian studies must adjust their analysis for the confounding effect of Asian dust. Accounting for this adjustment, hemorrhagic and ischemic stroke mortality in Japan between the years of 2005 and 2010 were still increased due to same-day spikes in suspended particulate matter.…”
Section: Air Pollution and Strokementioning
confidence: 99%